2021
DOI: 10.1016/j.autcon.2021.103826
|View full text |Cite
|
Sign up to set email alerts
|

Detecting visual design principles in art and architecture through deep convolutional neural networks

Abstract: Visual design is associated with the use of some basic design elements and principles. Those are applied by the designers in the various disciplines for aesthetic purposes, relying on an intuitive and subjective process. Thus, numerical analysis of design visuals and disclosure of the aesthetic value embedded in them are considered as hard. However, it has become possible with emerging artificial intelligence technologies. This research aims at a neural network model, which recognizes and classifies the design… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…repetition, compositional lines, contrast, balance, rhythm) (Demir et al, 2021). Effective use of visual design principles helps accomplish intended effects of communicating the visual design to viewers (Graves, 1951;Demir et al, 2021). Drawing from Berlyne's aesthetic theory (1971) and theory of grounded cognition (Barsalou, 2008), our findings demonstrated that repetition and compositional lines created by alignments evoke a multisensory experience involving visual appeal and imagined taste, making it easier for viewers to simulate tasting the presented food.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…repetition, compositional lines, contrast, balance, rhythm) (Demir et al, 2021). Effective use of visual design principles helps accomplish intended effects of communicating the visual design to viewers (Graves, 1951;Demir et al, 2021). Drawing from Berlyne's aesthetic theory (1971) and theory of grounded cognition (Barsalou, 2008), our findings demonstrated that repetition and compositional lines created by alignments evoke a multisensory experience involving visual appeal and imagined taste, making it easier for viewers to simulate tasting the presented food.…”
Section: Introductionmentioning
confidence: 74%
“…lines, color and shape) are visually organized (e.g. repetition, compositional lines, contrast, balance, rhythm) (Demir et al, 2021). Effective use of visual design principles helps accomplish intended effects of communicating the visual design to viewers (Graves, 1951;Demir et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As ML and AI methods are founded upon computational analysis (e.g., finite element method, FEA), building surrogate models to accelerate the assessment of architectural structure has been also investigated to facilitate design exploration (Wortmann et al, 2015; Zheng et al, 2020). Other approaches also include the evaluation of architectural designs in quantitative aspects, such as visual design principles, esthetics, and creativity (Mars et al, 2020; Demir et al, 2021). However, existing approaches still cannot address the challenges involving stone masonry designs: organizing heterogeneous shapes of natural stones in proper order considering the complex interaction across their joints, without prescribed knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the continuous development of theory and technology in the eld of arti cial intelligence (AI), its related research results have been widely used. For example, language recognition, image recognition, natural language processing, and other related achievements have brought a lot of convenience to all aspects of people's lives [1][2][3][4]. Robotics is one of the main technologies in the eld of AI.…”
Section: Introductionmentioning
confidence: 99%